Development of detection method for carcinogenic compounds using radish seeds Raphanus sativus, L via measuring the alkaline phosphatase enzyme activity - Efiana, Nuri Ari; Mulyadi, Mulyadi; Binarjo, Annas (Pharmaciana, 2023)
Convincing data regarding carcinogenic substances is very useful for handling materials correctly to avoid exposure to cancer-triggering substances in the body. To collect as much carcinogen data as possible, low-requirement carcinogen detection setups need to be developed. In this study, the first steps in the development of carcinogen detection through functional protein expression assessment are reported. Hydrazine sulfate, one of the well-known carcinogens chosen as a model material, was tested on germinating seeds of Raphanus sativus, L, with various concentrations, namely 0 (control), 1 mM, 10 mM, and 100 mM. Within a predetermined germination time, seeds and/or sprouts were observed and germination rate, protein concentration, and alkaline phosphatase activity were measured. The results showed that hydrazine sulfate slowed seed germination, and increased 72-h protein concentration but decreased alkaline phosphatase activity in the control group. This suggests that changes in alkaline phosphatase activity in seeds during germination have the potential to be a marker for cancer. In this research, it can be concluded that the method used can be applied as a first step to prove the carcinogenicity of a compound.